2020
DOI: 10.1177/0022167820940926
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity Is Correlated With Mindfulness and Emotional Intelligence

Abstract: Humanistic psychology has long been interested in authenticity. Carl Rogers proposed that authenticity leads to more fully functioning behavior. However, it is only in recent years that there has been empirical research into the correlates of authenticity. The aim was to test for association between authenticity and two individual difference factors of much contemporary interest—mindfulness and emotional intelligence. Participants were 197 adults recruited either through convenience sampling or an online surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Vess et al (2016) found that higher scores on the Cognitive and Affective Mindfulness Scale (Feldman et al, 2007) were associated with lower scores on Self-Alienation, r(93) = À.47, p , .01, higher scores on Authentic Living, r(93) = .29, p , .01, and lower scores on Accepting External Influence, r(93) = À.33, p , .01. In line with these results, Tohme and Joseph (2020) reported a strong correlation of r(197) = .61, p , .001, between the Kentucky Inventory of Mindfulness Skills (Baer et al, 2004) and the AS. The Kentucky Inventory of Mindfulness Skills includes four subscales: Observing, Describing, Acting With Awareness, and Accepting Without Judgment.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Vess et al (2016) found that higher scores on the Cognitive and Affective Mindfulness Scale (Feldman et al, 2007) were associated with lower scores on Self-Alienation, r(93) = À.47, p , .01, higher scores on Authentic Living, r(93) = .29, p , .01, and lower scores on Accepting External Influence, r(93) = À.33, p , .01. In line with these results, Tohme and Joseph (2020) reported a strong correlation of r(197) = .61, p , .001, between the Kentucky Inventory of Mindfulness Skills (Baer et al, 2004) and the AS. The Kentucky Inventory of Mindfulness Skills includes four subscales: Observing, Describing, Acting With Awareness, and Accepting Without Judgment.…”
supporting
confidence: 64%
“…Previous reports have shown that higher levels of authenticity correlate with higher levels of mindfulness (e.g., Tohme & Joseph, 2020), whereas true self-alienation (the feeling of being disconnected from what one truly is) is associated with mind wandering (Vess et al, 2016). On the other hand, the existing literature indicates that meditation fosters mindfulness experience (e.g., Moore & Malinowski, 2009) and reduces mind wandering (Mrazek et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, mindful people can be better at self-awareness, self-management, and social awareness (Goleman & Boyatzis, 2017). Previous studies support the link between trait mindfulness and emotional intelligence (Salcido-Cibrián et al, 2019;Tohme, 2020) Previous studies found a direct link between emotional intelligence and conflict management styles (Başoğul & Özgür;Schlaerth et al, 2013). For example, one study found that emotional intelligence is the antecedent of integrating and compromising styles (Shih & Susanto, 2010).…”
mentioning
confidence: 92%
“…Evidence supports his hypothesis by showing that authenticity is associated with various adaptive functioning and well‐being indicators across a range of contexts (see Sutton, 2020). For example, researchers have reported a positive association between authenticity and mindfulness, lower verbal defensiveness, higher secure self‐esteem, emotional intelligence, and psychological well‐being (Chen & Murphy, 2019; Heppner & Kernis, 2007; Lakey et al, 2008; Tohme & Joseph, 2020). In contrast, empirical evidence supports a link between inauthenticity and negative psychological outcomes.…”
Section: Introductionmentioning
confidence: 99%